Aerodynamic effects of road topography and meteorological conditions on time-trialling cycling performance - Marques-Bruna, P.; Grimshaw, P. (International Journal of Sports Science and Coaching, 2008)
This paper examines the interactive aerodynamic effects of road topography and meteorological conditions on time-trialling cycling performance. Aerodynamics and cycling performance were modelled using a fictitious cyclist completing a 40-km time-trial with simulated power outputs of 164 W (recreational level), 255 W (well-trained) and 394 W (elite). Virtual topographical conditions encompassed altitudes of up to 2500 m and ±2% road gradients. Meteorological variations incorporated 970-1040 mb barometric pressures, 0-40°C air temperatures, 0-100% relative humidity levels and ±2 m/s wind velocities. Interactions between physical altitude and weather were expressed in terms of the associated air density. Drag force was calculated, and aerodynamic power, cycling speed and finishing time were estimated using mathematical modelling. Prediction equations were developed using curve fitting. Non-standard atmospheric conditions alter the pressure altitude and density altitude of a particular race location. With increasing air density, drag force rises rapidly in direct proportion, but aerodynamic power increases and cycling performance declines in a non-linear fashion. Windy conditions and hilly terrain add to race time exponentially with air density. An Excel spreadsheet was developed which may be used by time-triallists to predict cycling performance and adjust pacing according to road topography and forecast weather.